"Being Bipolar": A Qualitative Analysis of the Experience of Bipolar Disorder as Described in Internet Blogs. (3rd October 2017) - Mandla, Anika; Billings, Jo; Moncrieff, Joanna
ABSTRACT: In the light of debates about the nature of bipolar disorder (BD), the current article presents a thematic analysis of Internet "blogs" by self-identified bipolar sufferers. Extreme and frequent fluctuation of mood was considered the principal feature of BD, along with a broad range of other problems. BD was often invoked as an explanation for life difficulties or lack of achievement, and was mostly regarded as a brain disease. Most bloggers emphasized the importance of drug treatment, along with the self-management techniques. The blogs present a "bipolar identity, " which is much broader than traditional definitions, are based on a medicalized model of the disorder, and are connected to the moral function of enabling people to externalize unwanted aspects of the self.